2023
DOI: 10.1039/d3py00207a
|View full text |Cite
|
Sign up to set email alerts
|

AnN-oxide containing conjugated semiconducting polymer with enhanced electron mobilityviadirect (hetero)arylation polymerization

Abstract: In this paper, an N-oxide building block, 4,4'-dimethyl-[2,2'-bithiazole] 3,3'-dioxide (MeBTzO), was designed and synthesized by oxidation of sp2- nitrogen in aromatic ring. Theoretical calculation results showed that MeBTzO has higher...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Unexpectedly, P3DPP-BT with three DPP blocks and one BT block in the repeating unit exhibits inferior transport characteristics with low electron/hole mobilities of 2 × 10 −2 /5 × 10 −2 cm 2 V −1 s −1 , respectively, causing a nearly 55 times decrease of electron mobilities compared with P2DPP-BT . Based on our previous research on ambipolar DPP-based polymers, 24 this work utilizes an acceptor modulation strategy to further improve the electron transport in the related DPP-polymers. As expected, the ambipolar charge transport behavior is observed in the three samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, P3DPP-BT with three DPP blocks and one BT block in the repeating unit exhibits inferior transport characteristics with low electron/hole mobilities of 2 × 10 −2 /5 × 10 −2 cm 2 V −1 s −1 , respectively, causing a nearly 55 times decrease of electron mobilities compared with P2DPP-BT . Based on our previous research on ambipolar DPP-based polymers, 24 this work utilizes an acceptor modulation strategy to further improve the electron transport in the related DPP-polymers. As expected, the ambipolar charge transport behavior is observed in the three samples.…”
Section: Resultsmentioning
confidence: 99%
“…17 It is found that the A-A backbone architecture could be fairly effective to deepen the lowest unoccupied molecular orbital (LUMO) energy levels, strengthen intermolecular interactions, and increase electron mobilities (m e ). [18][19][20][21][22][23][24][25][26] For instance, Guo et al developed a bis-diketopyrrolopyrrole (2DPP) based polymer P2DPP-TT (Fig. 1a), which shows stronger electron deficiency and intermolecular interactions than its single-DPP counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine-N-oxide has been shown to have similar properties as the tyrosine/tyrosyl radical redox couple and can thus serve as an electron shuttle in artificial photosynthesis (Figure 3D). 42,43 Along the same lines, polymeric N-oxides have been found to have special electron transport properties useful for the construction of semiconducting polymers 44 and interlayer materials for organic solar cells. 45 This special radical reactivity might also be the reason for the antioxidant properties, which have been suggested for several amphiphilic N-oxides used in cosmetic applications.…”
Section: Properties Of N-oxidesmentioning
confidence: 93%